Legal Protection Against Victims Of Share Results Application Fraud - Fitri Arianti (PT. Anagata Sembagi Education, 2024)
In the rapidly advancing era of digitalization, digital applications have become an integral part of everyday life, revolutionizing how we communicate, transact, and interact. However, along with these advancements come new challenges related to the misuse of technology, such as fraud that occurs through Share Results apps. This research aims to investigate the legal protection available to victims of fraud that occurs through such applications, recognizing the pressing need to address vulnerabilities in digital transactions. The research method employed is normative juridical, which involves analyzing the applicable laws and court decisions related to similar cases. By delving into legal frameworks and judicial precedents, the study seeks to elucidate the avenues of recourse available to victims of Share Results app fraud. The results of this research underscore the imperative for increased legal awareness among digital app users, improved regulation to respond to technological dynamics, and more effective law enforcement in dealing with digital crimes. Addressing these issues is essential for safeguarding the security and trust of users within an increasingly complex and dynamic digital ecosystem. Ultimately, the protection of Share Results app fraud victims emerges as a pivotal focus in broader efforts to fortify legal safeguards and ensure accountability within digital transactions. This endeavor is crucial for fostering resilience against emerging threats and fostering confidence in digital platforms.